Pengaruh Lama Penyimpanan Hasil Fermentasi Pelepah Sawit oleh Trichoderma Sp Terhadap Derajat Keasaman (pH), Kandungan Protein Kasar dan Serat Kasar - Achmad Jaelani; Neni Widaningsih; Eko Mindarto (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2015)
The purpose of this study was to determine the effect of storage lenght of fermented palm fronds by Trichoderma sp on the degree of acidity (pH), crude protein and crude fiber. This research used experiment with completely randomized design (CRD), which consists of 5 treatments and 4 replications. The treatment under study with storage time 0 weeks = control, 3 weeks, 6 weeks, 9 weeks and 12 weeks. Variables that are observed is the degree of acidity (pH), crude protein and crude fiber. Data were analyzed using analysis of variance if the treatment shows the real effect or very real then continued with test Duncan's Multiple Range Test (DMRT). The results showed that the storage time of fermented palm fronds by Trichoderma sp significantly affect the degree of acidity (pH) and crude fiber, but had no effect on levels of crude protein. Storage fermented palm fronds after 12 weeks can reduce the crude fiber content and pH.